KINERJA PERUSAHAAN PENGARUH DARI STRUKTUR MODAL, PROFITABILITAS DAN UKURAN PERUSAHAAN - Dede Hertina; Mohamad Bayu Herdiawan Hidayat; Fika Deningtyas (Journal of Management Small and Medium Enterprises (SMEs), 2021)
This study aims to determine the effect of Capital Structure, Profitability, Company Size on the Performance of the cigarette sub-sector companies listed on the IDX in 2014-2018. This research uses descriptive and verification methods with regression analysis tools and the coefficient of determination. The results of data processing analysis of the coefficient of determination obtained a fairly strong and unidirectional closeness of the relationship between the independent variable and the dependent variable and has a determination coefficient value of 47.91%. The results of testing the F test hypothesis indicate that the Capital Structure, Profitability and Company Size simultaneously have a significant effect on company Performance. Hypothesis testing using t test shows that Capital Structure has no significant effect on company Performance. Profitability has a significant effect on company Performance and Company Size has a significant effect on company Performance. Keywords: Capital Structure, Profitability, Company Size, Company Performance